A MOF-derived ZIF-8@Zn1−xNixO photocatalyst with enhanced photocatalytic activity. Issue 67 (30th August 2017) - Jing, Yanqiu; Wang, Jianan; Yu, Baohua; Lun, Jin; Cheng, Yuyuan; Xiong, Bin; Lei, Qiang; Yang, Yongfeng; Chen, Liangyuan; Zhao, Mingqin
Abstract : Today, metal doped ZnO exhibits good performances and attracts worldwide attention. Abstract : Today, metal doped ZnO exhibits good performances and attracts worldwide attention. In this paper, a ZIF-8@Zn1− x Ni x O photocatalyst was successfully prepared using MOF as precursor and AgNO3 as catalyst. We explored the influence of Ni content on the photocatalytic activity of ZIF-8@Zn1− x Ni x O. The structure and properties of ZIF-8@Zn1− x Ni x O were characterized by XRD, SEM, FT-IR, BET, UV-vis diffuse reflectance spectroscopy and so on. The results show that Ni is well loaded in ZIF-8 and part of ZIF-8 is oxidized to form Zn1− x Ni x O composites. The photocatalytic performance of ZIF-8@Zn1− x Ni x O was evaluated by degradation of rhodamine B (RhB) solution under UV light. It was found that ZIF-8@Zn0.95 Ni0.05 O exhibited the highest photocatalytic degradation efficiency and can degrade 99.19% rhodamine B solution after 20 min under UV light. Furthermore, ZIF-8@Zn0.95 Ni0.05 O exhibits high stability. After five repeated cycles, its photocatalytic activity remains at 97.43%.